Improved Control of PV System using Variable Step Size - Mohamed Lemine Bakayoko Yaye yébé; ENCA/ Mr. Messalti Sabir (University of M’sila, 2025)
In the present context, where industrial, economic, and ecological development are the priorities, photovoltaic energy stands as a favorable option when compared to the use of fossil fuels, which are known to be harmful to the environment. This study presents an improved Maximum Power Point Tracking (MPPT) method for photovoltaic systems based on a DC DC boost converter, using a variable step size method, compared to the drawbacks of the conventional algorithmic MPPT method. Therefore, five MPPT methods were analyzed and compared: the first is the P erturb and O bserve method with fixed step size, the second is the P&O method with variable step size, the third is the IC (Incremental Conductance) method with fixed step size, the fourth is the IC method with variable step size and the fifth is the PID (Proportional Integral and Derivative) controller. This study was carried out using a 100kW solar panel under fixed temperature and variable irradiation conditions in MATLAB/Simulink. The results show the effectiveness of variable step size in terms of fast response time, overshoot and accurate tracking of MPP.
Keywords: Photovoltaic system; Boost converter; Maximum Power Point Tracking; Perturbation and Observation; Incremental Conductance; Proportional Integral Derivative; Fixed Step Size; Variable Step Size.